Trianon néhány társadalmi-gazdasági hatása a Bánságban - Kókai, Sándor (Közép-Európai Közlemények, 2010)
At the end of the XIX century it became the most developed region inside the Carpathian Basin. The Trianon treatment have changed many economical and other problems (e.g. financial and national) and cut it down the traditional, economical and social connection. Today, the Bánság region is maybe born again. There is a new form of organization. They are looking for a place in the new globalizing world.